TGF-beta 1 and fibroblast growth factors selectively up-regulate tissue-specific fetal genes in cardiac muscle cells. - Parker,TG; Chow,KL; Schwartz,RJ; Schneider,MD (Ciba Found Symp, 1991)
TGF-beta 1, like basic and acidic fibroblast growth factor (FGF), inhibits differentiated gene expression in skeletal myoblasts. It potentiates FGF-beta 1 down-regulated expression of the alpha-myosin heavy chain gene and the sarcoplasmic reticulum calcium ATPase gene, yet up-regulated expression of the genes for beta-myosin heavy chain, atrial natriuretic factor, and both skeletal and smooth muscle alpha-actin-four transcripts associated with the embryonic heart. TGF-beta 1 did not affect cardiac alpha-actin gene expression. These responses resemble the generalized 'fetal' phenotype seen during hypertrophy triggered by a haemodynamic load. Chick skeletal and cardiac alpha-actin promoter-driven reported genes were transfected into neonatal rat cardiac myocytes. TGF-beta 1 stimulated skeletal alpha-actin transcription, but not transcription from the cardiac alpha-actin promoter. Basic FGF produced the same results as TGF-beta 1, but acidic FGF suppressed expression of both alpha-actin genes; these results were true for purified and recombinant FGFs. Modulation of alpha-actin transcription by growth factors corresponded accurately to control of the endogenous genes. Three positive cis-acting elements were critical for skeletal alpha-actin transcription in cardiac, as well as skeletal, myocytes, particularly the downstream CCAAT box-associated repeat. Thus, TGF-beta 1 and FGFs selectively induce an ensemble of 'fetal' genes and differentially regulate alpha-actin transcription in cardiac muscle cells.